Teachers’ Beliefs and the Flipped Classroom in Saudi Arabia: A Qualitative Study of Science Instruction - Fahdah Alanazi; Karthigeyan Subramaniam; Christopher Sean Long; Mila Rosa Librea-Carden; Nazia Khan (Scientia Publica Media, 2026)
This qualitative study, grounded in Dewey’s constructivist theory, explores how six Saudi Arabian secondary school science teachers view and use the flipped classroom as an active learning approach. The research adds to the growing conversation about science education in Saudi Arabia, especially in light of Saudi Vision 2030, which aims to bring more technology and innovative teaching strategies like the flipped classroom into schools. Using a case study design, the study draws on interviews, classroom observations, group discussions, and teaching materials to understand teachers’ beliefs. The findings show that teachers hold a mix of views about using the flipped classroom, including ideas about teaching science, their students’ learning, their own roles as teachers, and how all of this connects to the goals of Saudi Vision 2030. Teachers seemed most influenced by their beliefs about science teaching and their professional roles. The results suggest that teachers are more likely to adopt new teaching methods when those methods fit with what they already believe is effective. This highlights why it’s so important to consider teachers’ beliefs and experiences when rolling out new strategies like the flipped classroom as part of educational reforms. The findings yield two key implications. First, educational reforms introducing transformative instructional approaches, such as the flipped classroom, should explicitly account for teachers’ beliefs. Teachers’ belief systems are complex, dynamic, and central to instructional decision-making; consequently, they strongly influence whether new pedagogical approaches are adopted, adapted, or resisted. Ignoring these beliefs may limit the effectiveness and sustainability of reform efforts. Second, curriculum developers integrating flipped classroom approaches into science curricula should actively incorporate teachers’ perspectives during the design process. As practitioners with direct classroom experience, teachers possess critical insights into what is pedagogically viable, as well as the potential strengths and challenges associated with implementing innovative instructional strategies.